Synopsis and typification of New World members of the tribe Chiococceae (Rubiaceae, Dialypetalanthoideae) - Delprete, Piero G. (Journal of the Botanical Research Institute of Texas, 2025)
The tribe Chiococceae sensu Paudyal et al. (2018) is a monophyletic group of 30 genera and ca. 210 species. The tribe has amphi-Pacific geographical disjunction between the Neotropics and the West Pacific, with ca. 160 species present in the Greater Antilles, which represents its center of diversity, ca. 25 species present in Central and South America, and 28–30 species in the South Pacific (Philippines, New Caledonia, Marianas to Melanesia and Tonga Islands). The tribe has been shown to be monophyletic by numerous molecular phylogenetic studies. Members of the Chiococceae are highly variable in habit, ranging from subshrubs, erect or scandent shrubs, vines, treelets to tall trees. Their flowers are also highly variable in shape and dimensions, with corolla tubes ranging from ca. 3 mm long (e.g., Erithalis) to 27 cm long (e.g., Osa), with stamens inserted near or at the base of corolla tube or on the disc, and with spinulose pollen. Fruits of this tribe are also variable, as they can be capsular, drupaceous, or baccate, and the seeds can be flat, polygonal or globose, included in pyrenes or not. A synopsis of the Neotropical taxa of the tribe is here presented. The generic delimitations adopted in this synopsis follow those of Paudyal et al. (2018). The objective of this synopsis is to present a complete synonymy and typification of all the names involved, and to provide the identity of all the names of Neotropical taxa. A total of 83 lectotypifications, 20 neotypifications, and 1 epitypification, are here presented. The new combinations Coutaportla campanilla (DC.) Delprete, Scolosanthus crucifer ssp. microphyllus (Borhidi) Delprete, Solenandra coriacea (Poir.) Delprete, Solenandra parviflora (Bonpl.) Delprete, and the new species Scolosanthus nipensis Borhidi ex Delprete, are here published. In the Neotropics, 27 genera, 183 species, 8 subspecies, and 2 varieties, are here recognized in the tribe, of which 16 genera, 83 species, 5 subspecies, and 1 variety occur in Cuba.